2013
DOI: 10.1097/icu.0b013e32835f8bf8
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography – current and future applications

Abstract: Purpose of review Optical coherence tomography (OCT) has revolutionized the clinical practice of ophthalmology. It is a noninvasive imaging technique that provides high-resolution, cross-sectional images of the retina, retinal nerve fiber layer and the optic nerve head. This review discusses the present applications of the commercially available spectral-domain OCT (SD-OCT) systems in the diagnosis and management of retinal diseases, with particular emphasis on choroidal imaging. Future directions of OCT techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
326
1
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 491 publications
(358 citation statements)
references
References 64 publications
2
326
1
9
Order By: Relevance
“…The method, which is based on low coherence interferometry, was first presented by Huang et al [18]. In medicine, OCT is currently primarily used in ophthalmology for evaluating the pathological changes in retinal layers and the optic nerve [19][20][21][22]. Further applications are found in dermatology [23,24] and cardiology [25].…”
Section: Introductionmentioning
confidence: 99%
“…The method, which is based on low coherence interferometry, was first presented by Huang et al [18]. In medicine, OCT is currently primarily used in ophthalmology for evaluating the pathological changes in retinal layers and the optic nerve [19][20][21][22]. Further applications are found in dermatology [23,24] and cardiology [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, efforts are underway to provide automated choroidal thickness maps, similar to automated retinal thickness maps currently available, particularly with the coming next-generation OCT systems. 55 In conclusion, we observed that Sattler's medium vessel layer was disproportionately enlarged in sarcoid compared with TB-related uveitis, and there is a trend for the choroid to be thicker in active granulomatous uveitis. In addition, choroidal thinning was observed to be associated with reduced VA.…”
Section: The Choroid In Granulomatous Uveitismentioning
confidence: 56%
“…The OCT system is composed of a light source (ultra-short pulsed laser, super continuum laser or super luminescent diode), an interferometer, and a microscope that delivers light and collects reflection from the tissues analyzed. OCT is a technique for imaging tissues and cells in living organisms and is a diagnostic method that is widely used in cardiology [73], ophthalmology [74], dermatology [75], and also in other medical domains such as dentistry [76].…”
Section: The Use In Imagerymentioning
confidence: 99%